Nostalgia, Loss and Creativity in South-East Europe
XIII, 241 p. 21 illus., 14 illus. in color.
Keywords: Where nostalgia was once dismissed a wistful dream of a never-never land, the academic focus has shifted to how pieces of the past are assembled as the elements in alternative political thinking as well as in artistic expression. The creative use of the past points to the complexities of the conceptualization of nostalgia, while entering areas where the humanities meet the art world and commerce. This collection of essays shows how this bond is politically and socially visible on different levels, from states to local communities, along with creative developments in art, literature and religious practice. Bringing together scholars from a range of disciplines, the book offers analyses from diverse theoretical perspectives, united by an interest in the political and cultural representations of the past in South-East Europe from a long-term perspective. By emphasising how the relationship between loss and creative inspiration are intertwined in cultural production and history writing,these essays cover themes across South-East Europe and provide an insight into how specific agents – intellectuals, politicians, artists – have represented the past and have looked towards the future.